Effect of Different Fatty Acid Sources of Diet on Growth Performance of Botia Botia macracanthus Bleeker - Sunarto, .; Sabariah, . (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
Fish requires essential fatty acid for growth. Freshwater fish needs linoleat fatty acid (n-6) or combination of linoleat and a-linolenat acids (n-3). Fish oil contains higher level of n-3, corn oil is rich of n-6, while coconut oil is rich of saturated fatty acids. This study was conducted to determine the effect of fatty acid sources in diet on growth performance of botia Botia macracanthus. Sources of fatty acid examined were coconut oil (control), corn oil, fish oil, and corn oil + fish oil + coconut oil. The results of study show that daily growth rate of fish fed on diet containing mix of corn-coconut-fish oils (8.39%) and only corn oil (8.15%) was higher (p